RuO2 sputtered thin film supercapacitor's performance as function of oxygen incorporation - Lim, JH; Choi, DJ; Cho, WI; Yoon, YS (KOREAN PHYSICAL SOC, 2001)
The relation of oxygen incorporation of RuO2 film and Li+ ions is not clear as yet. To find it correlation between the capacitance and oxygen contents can provide the insight of mechanism and the improvement of performance. We sputtered the bottom electrode, RuO2 film oil Pt/TiO2/Si substrate in different oxygen partial pressure. Lipon (lithium phosphorous oxynitride) film it.,; all electrolyte was r.f. sputtered on it, and RuO2 film as it top electrode wits deposited oil Lipon with the same procedure of the first layer. In this work, we studied the effect of oxygen excess on the performance of TFSC. All solid-state TFSC was tested with charge-discharge cyclic measurement. It ran for 200 cycles. As the cycles go on, the capacitance decreases gradually. When oxygen partial pressure increased during RuO2 film deposition, the fade of capacitance rised.
Keywords: RUTHENIUM OXIDE